The integration of energy storage system in solar power generation: A bibliometric perspective of renewable energy - Norhana, Mohd Aripin; Suhaidah, Hussain; Lee, Khai Loon; Fatimah, Mahmud; Nur Sofia Nabila, Alimin (Emerald Publishing Limited, 2025)
Purpose: This study aims to review recent advancements in solar energy generation and identify future research trends, with a focus on integrating energy storage systems to enhance the reliability and efficiency of solar power. Design/methodology/approach: This study involved conducting a review of 313 articles published between 2014 and 2024 in the Scopus database. The research applied bibliometric analysis techniques, which are bibliographic coupling and co-occurrence analysis, to examine recent advancements and future trends in solar energy generation. Findings: This research highlights recent field contributions through bibliographic coupling, indicating that solar PV is the most environmentally sustainable renewable energy source, with energy storage systems, particularly hydrogen, critical for stability. In addition, co-occurrence analysis on the future research avenue highlights optimizing green hydrogen production and hybrid storage systems while exploring innovative financing models to enhance grid stability and facilitate a sustainable energy transition. Research limitations/implications: This review recognizes some limitations in bibliometric analysis, such as relying solely on the Scopus database, subjective interpretations of themes and the challenge of distinguishing self-citations from external ones, which can give a misleading impression of a publication’s influence. Originality/value: This study focuses on exploring how energy storage systems can be integrated with solar energy generation. Although there has been extensive research on renewable energy, this specific intersection has been largely overlooked. By using bibliometric analysis, this study aims to highlight recent developments and future directions in this critical area, ultimately providing valuable insights that can help shape both academic research and practical policy decisions.